Demonstration of 3 kW-Level Nearly Single Mode Monolithic Fiber Amplifier Emitting at 1050 Nm Employing Tapered Yb-Doped Fiber - Xiangming Meng; Yun Ye; Baolai Yang; Xiaoming Xi; Peng Wang; Chen Shi; Zhiyong Pan; Liangjin Huang; Hanwei Zhang; Xiaolin Wang (IEEE Photonics Journal)
Tapered Yb-doped fiber (T-YDF) can balance the suppression of transverse mode instability (TMI) and stimulated Raman scattering (SRS) in high power fiber lasers. In this work, we have constructed an all-fiberized master oscillator power amplifier emitting at the central wavelength of 1050 nm based on a T-YDF and investigated the laser performance in respective co-pumped and counter-pumped configurations. The results show that the T-YDF can effectively mitigate SRS effect in short-wavelength fiber lasers. A nearly single mode beam quality (M2∼1.20) is obtained at output power of 3 kW-level. In particular, the SRS suppression ratio in the co-pump and counter-pump scheme is about ∼33.2 dB at ∼3039 W and ∼46.6 dB at ∼2818 W, respectively. By further optimizing the structure of the tapered active fiber, it is promising to further improve the output power and beam quality in short-wavelength fiber lasers.